Perceptions of Undue Influence Shed Light on the Folk Conception of Autonomy - Niker, Fay; Reiner, Peter B.; Felsen, Gidon (Frontiers in Psychology, 2018)
Advances in psychology and neuroscience have elucidated the social aspects of human agency, leading to a broad shift in our thinking about fundamental concepts such as autonomy and responsibility. Here we address a critical aspect of this inquiry by investigating how people consider the socio-relational nature of their own agency, particularly the influence of others on their perceived control over their decisions and actions. Specifically, in a series of studies using contrastive vignettes, we examine public attitudes about when external influences on everyday decisions are perceived as “undue” – that is, as undermining the control conditions for these decisions to be considered autonomous – versus when they are perceived as appropriate and even supportive of autonomous decision-making. We found that the influence of preauthorized agents – individuals and institutions with whom we share a worldview – was judged to be less undue than non-preauthorized agents, even after controlling for the familiarity of the agent. These effects persisted irrespective of the extent to which respondents identified as communitarian or individualistic, and were consistent across two distinct scenarios. We also found that external influences that were rational were perceived as less undue than those that were arational. Our study opens new avenues of inquiry into the “folk conception” of autonomy, and we discuss the implications of our findings for the ethics of public policies designed to influence decisions and for information sharing in social networks.